Improvement of ribonucleic acid production in Cyberlindnera jadinii and optimization of fermentation medium - Mengting Li; Shuhong Gao; Pengcheng Yang; Hejin Li (AMB Express, 2024)
Abstract To enhance the ribonucleic acid (RNA) productivity for industrial applications, this study employed strain screening and medium optimization to improve the content of RNA in Cyberlindnera jadinii. A rapid screening method, combining atmospheric and room temperature plasma mutagenesis, 48-deep-well plates fermentation, and microplate reader detection, was developed. A mutant strain named WB15 with high RNA content was successfully obtained, exhibiting the RNA content of 156 ± 4.5 mg/g DCW, 1.4 times of the starting strain CCTCC AY 92020. Furthermore, Plackett–Burman design and response surface methodology were employed to identify three significant factors (yeast extract, soybean peptone, and KH2PO4) affecting the RNA content. By utilizing the optimal medium composed of 13.43 g/L yeast extract, 12.12 g/L soybean peptone and 2.78 g/L KH2PO4, the RNA content of WB15 further increased to 184 ± 4.9 mg/g DCW. Additionally, the mutant strain WB15 exhibited a greater cellular width compared to AY 92020, along with increased growth rate and single-cell RNA content by 22% and 48.9%, respectively. Perturbations in ribosome assembly, specifically a reduction in the ratio of ribosomal proteins to ribosomal RNA of the large subunit, might indirectly contribute to the higher RNA content in the WB15 strain. Overall, the combination of rapid screening with fermentation medium optimization proved to be an effective approach for improving the RNA content of C. jadinii, thus facilitating the industrial production of RNA.